2014
DOI: 10.1186/1475-2875-13-435
|View full text |Cite
|
Sign up to set email alerts
|

Net use, care and repair practices following a universal distribution campaign in Mali

Abstract: BackgroundThe Government of Mali and the President’s Malaria Initiative conducted a long-lasting, insecticidal net (LLIN) distribution campaign in April 2011 in the Sikasso region of Mali, with the aim of universal coverage, defined as one insecticide-treated net for every two persons. This study examines how households in post- and pre-campaign regions value and care for nets.MethodsThe study was conducted in October 2012 in Sikasso and Kayes in the southeast and western regions of Mali, respectively. The reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
4
16
0
Order By: Relevance
“…Nevertheless, a variety of barriers to bed net use exists. The findings in this study support earlier research highlighting discomfort due to heat and (low) perceived mosquito density as barriers to bed net use [9, 2325]. In addition, this study also indicated that outdoor sleeping is common throughout the hot and dry season, which runs from approximately October to April in the study area.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, a variety of barriers to bed net use exists. The findings in this study support earlier research highlighting discomfort due to heat and (low) perceived mosquito density as barriers to bed net use [9, 2325]. In addition, this study also indicated that outdoor sleeping is common throughout the hot and dry season, which runs from approximately October to April in the study area.…”
Section: Discussionsupporting
confidence: 89%
“…Formative research conducted in Senegal, Mali, Nigeria, and Uganda shows that attitudes around net care and repair are largely similar across these settings prior to BCC interventions [ 10 - 12 , 25 , 26 ]. Care and repair behaviours are not widespread and while respondents expressed anxiety about neighbours seeing their own torn or dirty nets, or view those with such nets as careless or lazy, there is also a clear lack of urgency to complete repairs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented higher access to ITNs, ACTs, and IRS coverage in PMI-recipient countries [1922] but have not compared these trends to non-recipient countries. More rigorous analysis of the association between PMI and key outcomes is needed to assess whether PMI was successful at curbing child mortality through implementation of evidence-based malaria interventions.…”
Section: Introductionmentioning
confidence: 99%